Konsep Kerjasama Mukhabarah di Bidang Pertanian Perspektif Ekonomi Islam - Anisa, Anisa (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This journal aims to explain the concept of cooperation in managing agricultural land based on the Islamic sharia system. This concept is justified in Islam. This concept is called mukhabarah, or we are usually familiar with the cooperation system in a business, especially in agriculture. This kind of cooperation system is still being debated among fiqh scholars; this is based on whether or not there are elements of usury, gharar, and maysir in the management concept. The approach used in this research is a qualitative normative star's approach, which examines a social phenomenon in more depth through Islamic sharia research studies and relates it to the phenomenon of cooperation mukhabarah that occurs a lot in society, especially in the agricultural sector. To describe how the concept of cooperation in the management of agricultural land is based on Islamic law, to provide benefits and not to distance the community from the element of harm, this study concludes that this type of cooperation system,